The first complete mitochondrial genome of the Grey-bellied Green Ratsnake Gonyosoma frenatum (Gray, 1853) and its phylogenetic placement - Le Wang; Bin Cai; Yan-Bin Huang; Hai-Ping Shangguan; Yan-Qing Wu (Mitochondrial DNA. Part B. Resources, 2021)
We sequenced the complete 17,209 bp mitochondrial genome (mitogenome) of Gonyosoma frenatum (Squamata: Colubridae) using next-generation sequencing. It consists of 13 PCGs, two ribosomal RNA genes, 22 transfer RNA genes, one non-coding region of an L-strand replication origin, and two control regions. The overall nucleotide composition was 34.7% of A, 24.8% of T, 12.3% of G, and 28.1% of C. The result of the phylogenetic analysis showed that G. frenatum, a member of Colubridae, is sister to other New World and Old World ratsnakes. The new data could help better understand the phylogenetic status of the genus Gonyosoma and the evolutionary history of Colubridae species.